Implementation and evaluation of an Exercise is Medicine™ on campus week. (October 2015) - Bopp, Melissa; Bopp, Christopher M.; Duffey, Michele L.; Ganim, Rebecca; Proctor, David N.
Highlights: Exercise is Medicine™ (EiM) on campus targets physical activity (PA) at colleges. This study describes the implementation of EiM on a large U.S. university campus. EiM week was implemented with campus PA stations and educational materials on PA. Evaluation included observations and surveys to assess awareness and reach. The study was successful in engaging a large, diverse population on a campus. Abstract: Exercise is Medicine™ (EiM) on campus targets physical activity (PA) participation on college campuses. Limited research has addressed how PA initiatives can be operationalized on college campuses. Purpose: To describe the implementation of EiM on a large U.S. university campus and present preliminary outcomes on participation and awareness. Methods: EiM week was implemented on a large university campus. Exercise stations were set-up at campus locations to encourage brief bouts of PA and educate about the benefits of PA. Evaluation included observations of participation, surveys, and intercept surveys to assess awareness and reach. Results: EiM week was implemented during Fall 2013. Exercise stations elicited 1771 exercise bouts from participants. Surveys indicated widespread reach across the university (13 of 17 colleges); most students (50.8%) became aware of the EiM campaign by passing by the exercise stations. Campus intercept surveys 1-week post-event indicated 54% students had heard about EiM, of which 39% had heard/seen the event through messages encouraging exercise. Conclusion: The current study was successful in engaging a large, diverse population on a college campus. Lessons learned from the development, implementation, and evaluation of EiM on campus activities provide insight for university campuses looking to target student health and PA participation.